(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Objective: Objective of this pilot study was to evaluate the reliability and internal consistency of the Columbia Impairment Scale questionnaire, as a tool to provide a global measure of impairment functioning in an Italian adolescents sample. Methods: The questionnaire is composed by 4 sections of functioning (interpersonal relations, broad psychopathological domains, functioning in schoolwork, use of leisure time) for a total of 13 items. It was administered twice in the same sample belonging to a Professional School in Frosinone (Central Italy), to 120 adolescents on the first administration and to 108 on the second time. Reliability analysis was performed and Cronbach’s alpha was used as a measure of internal consistency. Statistical analysis was performed using SPSS 19.0. Results: Considering all 13 items, Cronbach’s alpha amounted to 0,762 on the first time and to 0.826 on the second time, showing a very satisfactory internal validity. In the sample selected, the answers to the questionnaire showed adolescents have a low impairment functioning. Conclusion: The results of the pilot study indicate that the questionnaire presents a good reliability property and in terms of internal consistency and validity shows a good performance. The results are promising and suggest that this tool cood be used in the Italian setting for future research targeted to adequately capture the impaired functioning in adolescents.